Fraud Risk in Audit Activities According to IAS 8 - Raluca – Ionela Radu; Ciprian Tudurachi (Hyperion Economic Journal, 2014)
According to international auditing standards, fraud is an intentionally action realised by one or more persons as management, employees or third parties, action that generate erroneous interpretation of financial statements. The real intention is to cheat. However, there can be involved some erroneous calculus generated by creative accounting. The concept of “error” refers to unintentionally mistakes that could appear in financial statements. We think there could be mathematical or accounting mistakes, unintentionally omission, or wrong interpretation of certain facts, accounting policies wrong application. All these actions are unwittingly. It is very important to identify situations cause and take necessary measures to eliminate them